Perlindungan Hukum Bagi Petani Korban Penipuan Jual Beli Bawang Merah(Studi di Kecamatan Sambi Rampas Kabupaten Manggarai Timur Provinsi Nusa Tenggara Timur) - Nur Fadilah Al Idrus; Rufaidah (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Sale and purchase of shallots by farmers and traders in Sambi Rampas sub-district based on trust and verbal agreement. The purpose of writing is to examine the problems of buying and selling shallots in Kec. Sambi Rampas and analyzing the impact of these transactions and proposing efforts to prevent fraud. Research method: empirical legal research. Legal materials: primary, secondary. Approach method: Case, Concept. Result: The problem of buying and selling shallots in Sambi Rampas District started with one of the successful traders committing mass fraud against farmers in 2015 and lasted until 2020. taken by the police through a compensation agreement but in fact the settlement for several years was not evenly distributed among all the farmers who were victims. The main cause was because the victim did not have proof of the purchase contract so the perpetrator did not admit that he had bought the victim's shallots. In fact, if farmers enforce formal contracts in their transactions, there will be no traders who want to buy their shallots. Suggestion: The police as law enforcement officers need to ensure the security of transactions for both parties, so the involvement of the police is needed, especially in large purchases and if the perpetrators of fraud escape, efforts are made to resolve cases firmly and seriously so as to gain the trust and satisfaction of the local community.